Pembangunan Sistem Electronic Customer Relationship Management pada PT. Beton Elemenindo Perkasa - Faizal Zaenal Hambali; Wina Witanti; Puspita Nurul Sabrina (Komputika : Jurnal Sistem Komputer, 2019)
PT. Beton Elemenindo Perkasa is a company engaged in the construction industry as a provider of precast concrete for infrastructure projects both government and private projects. The company was founded on February 5, 1990. PT. Beton Elemenindo Perkasa markets its products in a conventional way, which comes directly to the customer, but inadequate product and service promo information makes it difficult for the company to retain customers. In addition, the lack of communication media from the company causes a lack of assessment and evaluation of the company's performance in an effort increasing demand will have an impact on decreasing loyalty and if it happens continuously the company will lose customers or switch customers to other companies. Possibility of developing a Customer Relationship Management system at PT. Beton Elemenindo Perkasa will use the waterfall method. Keyword - Electronic Customer Relationship Management; PT. Beton Elemenindo Perkasa; Waterfall.